The wh-questions of network meta-analyses - De Giorgi, R (Cambridge University Press, 2019)
Currently, network meta-analyses (NMAs) are the only technique allowing to compare and rank numerous treatments across trials. Evidence produced by NMAs relies on pooled data from both direct and indirect comparisons within the studies. As such, NMAs are invaluable tools for informing clinical guidelines.